Unpaid Work and the Economy - Picchio, Antonella; Picchio, Antonella (Taylor & Francis, 2003)
In economics, the voluntary sector is surprisingly understudied. In order to fully understand economics, unpaid and voluntary work needs to be taken into account and afforded the same status as paid activities. This book constitutes a rigorous economic analysis with special emphasis on gender issues and covers every conceivable angle of unpaid work and all its ramifications for the modern economy. The unified vision offered by this group of leading contributors ensures this book is a work of excellent quality. There is every chance it will become a seminal study on unpaid work and as such will provide a useful reference for students and academics involved in gender studies, econometrics, and consumption studies.
English
Keywords: Economics; Business & management; extended; income; equivalency; scale; womens; labour; market; convenience; consumption; double